Conservação de mamão formosa submetido a diferentes tratamentos pós-colheita - Ramalho Neta, Terezinha (Universidade Federal Rural do Semi-Árido, 2017)
Papaya is characterized by a relatively short post-harvest shelf life, completing its ripening in approximately one week under ambient conditions, and several pre and post harvest factors, such as pathogens or abiotic factors, may reduce its conservation potential. The objective of the present work was to evaluate the effect of the application of atmospheric plasma, peracetic acid, hydrothermal treatment and wax on the conservation and incidence of post-harvest diseases of Formosa 'Tainnung, 01' papaya subjected to refrigerated storage. The fruits were obtained from a commercial orchard, located in the city of Baraúna - RN. A total of 106 fruits with maturation stage 1 (fruit with up to 25% of the yellow peel) were collected and taken to the Post-harvest Laboratory of the Universidade Federal Rural do Semi-Árido (UFERSA), where the experiment was set up in a completely randomized design with factorial scheme 4 x 5 (treatment x storage time), with three replicates and three fruits for each. The treatments were as follows: T1 (Witness) fruits without washing; T2 Hydrothermal (48 ± 1 ° C for 30 minutes) plus wax; T3 Atmospheric plasma; T4 Carnauba wax; T5 Peracetic acid plus wax. After application of the treatments the fruits were stored under refrigeration (9.7 ± 1 ° C and 76 ± 5% RH). The fruits of the hydrothermal treatment presented inferior appearance and high incidence of diseases, when compared to the other treatments, with their useful life limited in 8 days. The fruits treated with peracetic acid, wax and plasma had their appearance compromised by the incidence of disease during storage, however, at 32 days of storage they were still looking reasonable and fit for consumption. However, the fruits treated with plasma presented disease incidence on the 24th day of storage, and the fruits of the hydrothermal treatment and the control at 16 days of storage. During storage, the following pathogens were identified in the fruits: Alternaria sp., Phytophthora sp and Fusarium sp.
Monografia
Keywords: Carica papaya L.; Vida útil pós-colheita; Qualidade; Doença pós-colheita; Carica papaya L.; post-harvest shelf life; quality; post-harvest disease; CIENCIAS AGRARIAS::AGRONOMIA